EVALUATION OF INSECTICIDES RESISTANCE IN Blattella germanica (L., 1757) (Dictyoptera: Blatellidae) IN JUIZ DE FORA MUNICIPALITY, MINAS GERAIS, BRAZIL - Furiatti de Souza, Wander Luiz; Abreu, Paula Ferreira de; Ramos dos Reis-Menini, Cintia Moreira [UNESP]; Menini Neto, Luiz (Univ Federal Uberlandia, 2011)
Blattella germanica lives a long time in association with the man, near man's food and creating resistance to various insecticides. Thus, it is the species of cockroach more difficult to control, causing great disorder, affecting the economy and presenting medical importance. This study aimed to evaluate the resistance of B. germanica to Diazinon (R) (organophosphate), Cipermetrine (R) (pyrethroid) and Propoxur (R) (carbamate) insecticides and the period of residual effect assessed until 15 days of application. In order to evaluate the acquired resistance by B. germanica to insecticide and for better characterization with the day by day of the companies that control pests, the dilution in water followed the instructions of the manufacturer and technique for the test was tarsal contact. The cockroaches were collected in many locations in commercial areas in Juiz de Fora municipality (Minas Gerais) and created in laboratory environment (temperature 28 degrees C +/- 1 degrees C, 60% +/- 5% relative air humidity), feeding with dog food, powdered milk and water, offered continuously. The specimens obtained from the 3(rd) generation were used in the tests, eliminating any previous contact with insecticide or other chemical products. For evaluation of each insecticide were used 1800 specimens. The results showed resistance to Cipermetrine and Propoxur, while Diazinon was the most effective, proving to be the best recommendation for the control of this insect. The residual effect of the three insecticides showed similar results for the control of B. germanica and the most stable period was from the 1(st) to the 10(th) day.
Keywords: German cockroach; Cipermetrine; Propoxur; Diazinon; Urban pest management